2021
DOI: 10.1210/clinem/dgab171
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effect of Prepregnancy Overweight/Obesity and Isolated Maternal Hypothyroxinemia on Macrosomia

Abstract: Context Pre-pregnancy overweight/obesity (OWO) and isolated maternal hypothyroxinemia (IMH) may increase the risk of macrosomia, but little is known about their potential combined effect on macrosomia. Objective The aim of this study was to assess whether pre-pregnancy OWO and first-trimester IMH have a synergistic effect on the risk of macrosomia. Design A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
11
2
Order By: Relevance
“…Advanced peripheral deionization to decrease plasma FT4 levels has been reported in obese individuals [ 6 , 24 ]. Contrary to our study, 2 Chinese cohorts [ 20 , 21 ] and a Caucasian cohort from the United States [ 19 ] suggested an increased risk of macrosomia in isolated hypothyroxinemia during the first trimester. In these reports, maternal BMI and the prevalence of overweight/obesity were much higher than our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Advanced peripheral deionization to decrease plasma FT4 levels has been reported in obese individuals [ 6 , 24 ]. Contrary to our study, 2 Chinese cohorts [ 20 , 21 ] and a Caucasian cohort from the United States [ 19 ] suggested an increased risk of macrosomia in isolated hypothyroxinemia during the first trimester. In these reports, maternal BMI and the prevalence of overweight/obesity were much higher than our study.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study of 19,622 singleton pregnancies suggested that maternal GDM status increased the risk of macrosomia independently and synergistically with pre-pregnancy overweight ( 9 ). Despite widespread screening and management of GDM, the prevalence of macrosomia remains relatively high among pregnant women without GDM, which indicates that some other factors may also influence the incidence of macrosomia ( 10 ). It is reported that advanced maternal age ( 11 ), male fetuses ( 12 ), higher parity ( 13 ), and certain season of delivery ( 14 ) were also associated with increased odds for fetal macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal overweight/obesity is closely related to the birth weight of newborns. 23,24 However, pre-BMI stratification was not included in the LASSO regression analysis in our logistic regression model. We speculate that it might be related to the obesity character of the GDMresistance subtype, which leads to the limited importance of pre-BMI in the logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal overweight/obesity is closely related to the birth weight of newborns 23,24 . However, pre‐BMI stratification was not included in the LASSO regression analysis in our logistic regression model.…”
Section: Discussionmentioning
confidence: 99%